A Dermal Equivalent Engineered with TGF‐β3 Expressing Bone Marrow Stromal Cells and Amniotic Membrane: Cosmetic Healing of Full‐Thickness Skin Wounds in Rats. Issue 12 (December 2016) - Samadikuchaksaraei, Ali; Mehdipour, Ahmad; Habibi Roudkenar, Mehryar; Verdi, Javad; Joghataei, Mohammad Taghi; As'adi, Kamran; Amiri, Fatemeh; Dehghan Harati, Mozhgan; Gholipourmalekabadi, Mazaher; Karkuki Osguei, Nushin
Abstract: Transforming growth factor beta‐3 (TGF‐β3) has been shown to decrease scar formation after scheduled topical applications to the cutaneous wounds. This study aimed to continuously deliver TGF‐β3, during the early phase of wound healing, by engineering a dermal equivalent (DE) using TGF‐β3 expressing bone marrow stromal cells (BM‐SCs) and human dehydrated amniotic membrane (hDAM). To engineer a DE, rat BM‐SCs were seeded on the hDAM and TGF‐β3 was transiently transfected into the BM‐SCs using a plasmid vector. Pieces of the dermal equivalent were transplanted onto the full‐thickness excisional skin wounds in rats. The process of wound healing was assessed by image analysis, Manchester Scar Scale (MSS), and histopathological studies 7, 14, 21, and 85 days after the excision. The results confirmed accurate construction of recombinant pcDNA3.1‐TGF‐β3 expression system and showed that the transfected BM‐SCs seeded on hDAM expressed TGF‐β3 mRNA and protein from day 3 through day 7 after transfection. After implantation of the DE, contraction of the wounds was measured from day 7 through 21 and analyzed by linear regression, which revealed that the rate of wound contraction in all experimental groups was similar. Histologic evaluation demonstrated that transfected BM‐SCs decreased retention and recruitment of the cells during the early stage of wound healing, decreased the formation of vascular structures and led to formation of uniformly parallel collagen bundles. MSS scores showed that TGF‐β3 secreting cells significantly improved the cosmetic appearance of the healed skin and decreased the scar formation. From these results, it could be concluded that transient secretion of TGF‐β3, during the early phase of healing, by BM‐SCs seeded on hDAM can improve the cosmetic appearance of the scar in cutaneous wounds without negatively affecting the process of wound repair.